1991
DOI: 10.1073/pnas.88.1.291
|View full text |Cite
|
Sign up to set email alerts
|

Selection of suppressor methionyl-tRNA synthetases: mapping the tRNA anticodon binding site.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 27 publications
5
62
0
Order By: Relevance
“…Extensive experiments have been carried out to establish the importance of several amino acid residues in MetRS and the nucleotides of tRNA in the recognition processes. For instance, the loop containing highly conserved residue Trp-461 plays a crucial role in the recognition of anticodon bases, as confirmed by affinity-labeling experiments (5), isolation of second site mutants (6), and docking studies of glutaminyl-tRNA on MetRS (7). Substitution of highly conserved residues Trp-461, Asn-452, or Arg-395 shows their involvement in the binding of MetRS to anticodon site of tRNA (8)(9)(10).…”
mentioning
confidence: 99%
“…Extensive experiments have been carried out to establish the importance of several amino acid residues in MetRS and the nucleotides of tRNA in the recognition processes. For instance, the loop containing highly conserved residue Trp-461 plays a crucial role in the recognition of anticodon bases, as confirmed by affinity-labeling experiments (5), isolation of second site mutants (6), and docking studies of glutaminyl-tRNA on MetRS (7). Substitution of highly conserved residues Trp-461, Asn-452, or Arg-395 shows their involvement in the binding of MetRS to anticodon site of tRNA (8)(9)(10).…”
mentioning
confidence: 99%
“…The mutant genes were cloned in specialized pUCl2-derived expression vectors (Mechulam et al, 1991 b) and expressed in JMlOlTr cells (Hire1 et al, 1988) in the presence of 0.3 mM isopropyl b-D-thiogalactoside. B. stenrothermophilus MS.534 variants were then purified to homogeneity using a procedure similar to that described in the case of E. coli MetRS (MetRS-EC) (Meinnel et al, 1991). Two chro- matographic steps were performed in 10 mM potassium phosphate pH 7.3, 50 mM potassium chloride and 10 mM 2-mercaptoethanol, firstly on a Superose-6 molecular sieve (Pharmacia; 1.6X50 cm; 0.2 ml/min) and secondly on a Q-Hiload anion exchanger (Pharmacia; 1.6X10 cm; 2.5 mumin; 100 mM/h potassium chloride).…”
Section: Methodsmentioning
confidence: 99%
“…2). Mutagenesis studies of E. coli MetRS and selection of second-site mutants showed that the region surrounding Trp461 (called region 460) played a crucia1 role in this process (Ghosh et al, 1990;Meinnel et al, 1991;Schmitt et al, 1993). In addition to Trp461, Asn452 is involved.…”
Section: Characterization Of the Methionine And Zinc Binding Sitesmentioning
confidence: 99%
See 2 more Smart Citations